BPM을 기반으로 한 ISO 9001 품질경영시스템 구축 - 김상국(Sang-Kuk Kim); 신성호(Sung-Ho Shin) (한국콘텐츠학회 논문지, 6(4), 2006)
Most organizations adopt a process-based approach to manage their operations and now business process management(BPM) is a well-established concept. Because ISO 9001:2000 has been influenced by BPR and it also emphasizes process based, BPM can get together with ISO 9001:2000. Korea Institute of Science and Technology Information has taken ISO 9001:2000 certificate in November 11, 2003 and has implemented quality management systems based on BPM. We call it KQMS(KISTI Quality Management System). KQMS based on BPMS is a new example in field of ISO quality management and is expected to support process management well. 오늘날 대부분의 조직들은 프로세스 중심의 업무 관리를 위해 노력하고 있고, 이를 위한 Business Process Management(BPM)의 개념은 점차 확산되어 가고 있는 추세이다. ISO 9001:2000 품질경영시스템이 Business Process Re-engineering(BPR)의 영향을 받았고, 프로세스 중심적인 경영시스템이기 때문에, BPM은 ISO 9001:2000 품질경영시스템과 다르지 않다고 본다. 한국과학기술정보연구원(KISTI)은 2003년 11월 11일에 ISO 9001:2000 인증은 받았고, BPM 기반의 품질정보시스템을 구축하였다. KISTI의 품질정보시스템은 BPM을 기반으로 하여 프로세스 경영을 잘 지원할 것이며, BPM과 품질경영을 접목한 새로운 사례가 될 것이다.